Pengaruh Kualitas Kehidupan Kerja Terhadap Komitmen Organisasional Dengan Kesejahteraan Karyawan Sebagai Variabel Mediasi (Studi pada Karyawan Peternakan Ayam Petelur di Kecamatan Purbolinggo, Kabupaten Lampung Timur) - Delia Indriani; Ribhan Ribhan; Mirwan Karim (Journal on Education, 2024)
The phenomenon of employees resigning from their company or the low level of organizational commitment in employees is thought to be caused by poor quality of work life, besides the role of employee welfare to mediate between the influence of quality of work life on organizational commitment. The purpose of this study is to determine whether there is a direct effect of quality of work life on organizational commitment and whether the indirect effect of employee welfare can mediate the effect of quality of work life on organizational commitment. This research uses a type of quantitative research. This study uses primary data obtained by distributing questionnaires directly through questionnaires at CV Sekuntum Herbals and PT Sanjaya Satwa Utama, the data obtained is then processed using the AMOS SEM analysis tool. The population in this study were employees of CV Sekuntum Herbals and PT Sanjaya Satwa Utama who had worked for at least one year and obtained the results of respondent data that met the criteria of 128 people. So that a sample of 120 respondents was obtained because there were 3 questionnaires that were not returned and 5 questionnaires that were not filled in completely. The results of this study are that the quality of work life has a significant positive effect on organizational commitment, then employee welfare mediates positively and significantly between the influence of work life quality on organizational commitment.